Programa educativo ambiental para desarrollar la actitud ecológica de los estudiantes del 6° de la I.E. Rafael Narváez Cadenillas, 2010 - Zavaleta Soria, Silvia Marleni (2012)
The present thesis entitled "Environmental Education Programme to develop the ecological attitude in students from the 6 ° of I. E. Rafael Narvaez Cadenillas, 2 011"; aimed at develop the ecological attitude, at the same time, expand and deepen their knowledge in environmental education (EA). The sample consisted of 31 students which was administered a pretest and a year to measure, analyze and explain their ecological attitude on the side reactions: cognitive, affective and tendency to action or conduct. By working with a single group -sampling type probability – the study of applied research wasn’t pre-experimental. Global outcomes stated that the implementation of the environmental education program developed ecological attitude in students of I. E. "Rafael Narvaez Cadenillas". Has been effective in relation to the three components, because they demonstrate particular actions for improvement in their ecological attitudes. I would therefore conclude that the hypothesis was confirmed that the application of the Environmental Education Program developed the ecological attitude of the students because there is statistical significance between the vast majority of responses, as demonstrated by the test "t student".